Advances in accounting behavioral research. Vol. 3 - Hunton, James E. (Emerald, 2000)
Part 1: Perspectives on Behavioral Research in Accounting. Where have all the leaders gone? (S. Sutton). Part II: Accounting Behavioral Research. A new culture? Evidence of support for diversity in public accounting performance evaluation judgments (E.N. Johnson et al.). Auditor work and its outcomes: an application of the job characteristics model to large public accounting firms (T.J. Fogarty, B. Uliss). Evaluating audit risk: the effects of tolerence-for-ambiguity, industry characteristics, and experience (B.A. Makkawi, R.W. Rutledge). The effect of role stress on budgetary participation and job satisfaction-performance linkages: a test of two different models (V.K. Chong, D. Bateman). The early identification of managerial motivation: an empirical examination (S.M. Bryant et al.). The influence of attributions and budget emphasis and risk preferences under conditions of unfavorable budget variances (D. Ryan, K. Wentzel). Accuracy and calibration in professional judgment: a study of tax practitioners (D. Samelson, C. Jeffrey). Relational demography and career outcomes among male and female academic accountants (C. Kirchmeyer et al.). Part III: Accounting Behavioral Theory. Creating an ethically driven organization: a model for fostering an epidemic of ethical intensity (V. Arnold et al.). Belief functions in accounting behavioral research (R.P. Srivastava, T.J. Mock). Theoretical reflections on the use of students as surrogate subjects in behavioral experimentation (M. Walters-York, A.P. Curatola). E-research: moving behavioral accounting research into cyberspace (T.L. Herron, G.R. Young, II).
Keywords: Business & Economics -- Accounting -- General.; Science -- History.; Accounting.; Accounting -- Psychological aspects -- Research.; elektronické knihy; electronic books